SANKSI PIDANA DALAM TINDAK PIDANA PERDAGANGAN ANAK DI INDONESIA - Parwata Tri Bwana, I.G.A; Retno Murni, R.A (Kertha Wicara : Journal Ilmu Hukum, 2013)
Child trafficking is a form of crime which violates the basic human rights. Fragile lawenforcement especially within the perspective of human rights in Indonesia is mainlydriven by incomprehensive law enforcement. Due to that, legal certainty and warrantyshall never be put into reality and weakens the supremacy of law itself. In currentcondition, violence had reflected a miserable human rights promotion, respect, andfulfillment.
Keywords: Child Trafficking, Human Rights Violation, Penal Sanction